2004
DOI: 10.1080/00480169.2004.36419
|View full text |Cite
|
Sign up to set email alerts
|

Effect of liveweight and condition score of ewes at mating, and shearing mid-pregnancy, on birthweights and growth rates of twin lambs to weaning

Abstract: Liveweight and condition score of ewes at mating had small positive effects on growth rates to weaning of twin lambs. Shearing mid-pregnancy increased birthweights and weaning weights of twin lambs. To achieve high weaning weights of twin lambs, farmers should ensure ewes attain high liveweights and condition scores at mating and shear mid-pregnancy. It is speculated that the effects of liveweight and condition score of ewes at mating on weaning weights of twin lambs would be greater than those observed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
32
1
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 10 publications
(2 reference statements)
9
32
1
7
Order By: Relevance
“…However, little effect was observed in ewes offered a level of herbage which maintained maternal weight. In contrast, Kenyon et al (2004a) reported a small positive relationship between the weight of ewes at mating and birthweights of twin lambs (0.02 kg/kg liveweight of the dam) under conditions in which the total weight of ewes increased at a level similar to the expected weight of the conceptus at term. Similarly, in the present study liveweight of the hoggets pre-breeding had a small positive effect on singleton lamb birthweights (0.046 kg/kg liveweight of dam) under conditions in which the total weight of hoggets increased at a level similar to the expected weight of the conceptus at term.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, little effect was observed in ewes offered a level of herbage which maintained maternal weight. In contrast, Kenyon et al (2004a) reported a small positive relationship between the weight of ewes at mating and birthweights of twin lambs (0.02 kg/kg liveweight of the dam) under conditions in which the total weight of ewes increased at a level similar to the expected weight of the conceptus at term. Similarly, in the present study liveweight of the hoggets pre-breeding had a small positive effect on singleton lamb birthweights (0.046 kg/kg liveweight of dam) under conditions in which the total weight of hoggets increased at a level similar to the expected weight of the conceptus at term.…”
Section: Discussionmentioning
confidence: 80%
“…It is known that "fat" mature ewes produce more milk than thin ewes (Rattray 1986) during periods of restricted feeding as their body reserves can be used to support milk production, especially in twin-suckling ewes. Both McCall et al (1986) and Kenyon et al (2004a) reported a positive effect of pre-lambing weight of mature ewes on lamb growth. Similarly, late pregnancy liveweight and body condition of mature ewes has been reported to positively effect growth rates of lambs (Gibb & Treacher 1980;Wilson et al 1985;Hossamo et al 1986).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lamb growth to weaning is influenced by lamb birth weight and dam milk production (Peart 1967;o'Connor 1996;Muir et al 1998;Kenyon et al 2004a). Milk production itself is affected by ewe pregnancy rank, body condition and liveweight of the ewe and her nutrition in pregnancy, and size of lamb at birth (Peart 1967;Treacher 1970;Rattray 1986;Bencini & Pulina 1997;Muir et al 1998;Bizelis et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Shearing ewes between days 50 and 100 of pregnancy has been identified as a technique that consistently increases lamb birth weight under pastoral (Kenyon et al 2004;Corner et al 2007) and winter-housed, sheep management systems (Dyrmundsson 1991). This increased birth weight has also been associated with an increase in lamb survival rates to weaning (Morris et al 1999;Kenyon et al 2006).…”
Section: Introductionmentioning
confidence: 99%